FAKTOR RISIKO KECELAKAAN KERJA NELAYAN - Idham Latif; Rudiansyah -; Depi Yulyanti (JURNAL KESEHATAN INDRA HUSADA, 2020)
In carrying out fishing activities, fishermen often face the risk of work accidents. Two factors cause accidents, which are unsafe actions and unsafe conditions. The work activities of Pantura fishermen did not escape the risk of workplace accidents. From 2013-June 2014 in the port of Karangsong Indramayu recorded 29 cases of accidents with 39 victims lost/died. Research is needed to analyze risk factors for the work accident of Pantura fishermen. The study population was Pantura fishermen, with 116 cases and control samples. The dependent variable was the accident event, the independent variable consisted of action and condition . Design a case-control study with a questionnaire as a data collection tool. Analysis with multiple linear regression statistical tests. The results of the study found that there was a significant relationship (α=5%) between unsafety action with a work accident (p=0,000) with an odds ratio of 8.25. Some risk factors for unsafety action after calculating the effect together are sub-variables: using a damaged safety device with an odds ratio of 6.577, and joking in the workplace with an odds ratio of 6.33. The research found that joking in the workplace is 6 times the risk for accidents compared to non-jokes in the workplace.